2014
DOI: 10.1155/2014/419570
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Corrosion Products on Carbon Steel Exposed to Natural Weathering and to Accelerated Corrosion Tests

Abstract: The aim of this work was to compare the corrosion products formed on carbon steel plates submitted to atmospheric corrosion in urban and industrial atmospheres with those formed after accelerated corrosion tests. The corrosion products were characterized by X-ray diffraction, Mössbauer spectroscopy, and Raman spectroscopy. The specimens were exposed to natural weathering in both atmospheres for nine months. The morphologies of the corrosion products were evaluated using scanning electron microscopy. The main p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 24 publications
6
24
0
5
Order By: Relevance
“…Further EDS analysis of these crystals revealed that they were 44% oxygen, 24% sulfur, and 31% calcium by weight. These mass ratios correlate stoichiometrically to the mass ratios of calcium sulfate, which has been described in the literature with similar crystal dimensions [22]. The presence of sulfates in these specimens was not surprising in light of the presence of sulfates in the seawater [11].…”
Section: Corrosion Product Observationssupporting
confidence: 72%
See 1 more Smart Citation
“…Further EDS analysis of these crystals revealed that they were 44% oxygen, 24% sulfur, and 31% calcium by weight. These mass ratios correlate stoichiometrically to the mass ratios of calcium sulfate, which has been described in the literature with similar crystal dimensions [22]. The presence of sulfates in these specimens was not surprising in light of the presence of sulfates in the seawater [11].…”
Section: Corrosion Product Observationssupporting
confidence: 72%
“…In the literature, these small crystal nodules viewed in the SEM image of Figure 3 are commonly associated with the presence of lepidocrocite, while the flattened background region appeared to be characteristic of magnetite (Fe 3 O 4 ) [22]. The prismatic crystals viewed in two of the locations sampled were approximately 5 μm (2 mil) in width.…”
Section: Corrosion Product Observationsmentioning
confidence: 75%
“…SEM micrographs of the surface confirm the results of the Raman tests. As observed in Figure 3, sandy crystals of lepidocrocite [27,28] and cigar-like crystals of akaganeite can be observed on the surface.…”
Section: Belle Marementioning
confidence: 74%
“…This can be confirmed from the SEM micrographs in Figure 9. Fine whiskers of lepidocrocite [26,28] were observed on the surface which consisted of a loose structure that led to a high initial corrosion rate [29]. Figure 10.…”
Section: Port Louismentioning
confidence: 99%
“…However, in studies characterizing the composition of carbonation induced corrosion products formed in concrete, or in other situations such as atmospheric corrosion of steel, the corrosion products have always been found to be composed of compounds with iron in the oxidation state +3 [23][24][25][26]. This is because there is an intermediate transformation, that is the spontaneous and fast oxidation reaction of Fe 2+ ions , which involves oxygen and hydroxyl ions and leads to the final formation of Fe 3+ (eq.…”
Section: Formation Of Corrosion Productsmentioning
confidence: 99%